Implementing IBS Technology of Reducing Costs Problems for Affordable Housing Project - Mohd Nizam, Nurina Batrisyia; Zainal, Rozlin; Abd Rahim, Mohd Hilmi Izwan; Shamsudin, Zarina (Research in Management of Technology and Business, 2024)
Industrialised Building System (IBS) technology has long been introduced in Malaysia since early 1960 and now its use is growing as it gives many advantages in construction especially in saving time and cost. This technology is able to address the issue of affordable housing which is a hot topic at the moment due to the rise of demand and need as well as the issue of widespread use of IBS technology in the housing construction sector is the increasing cost of building materials that led to an incremental increase in housing costs. Therefore, the objectives of this research are to identify the main problems of implementing IBS technology of reducing costs for affordable housing project, to identify the main solutions of implementing IBS technology of reducing costs for affordable housing project and to examine the relationship between the main problems with main solutions of implementing IBS technology of reducing costs for affordable housing project. This research used a quantitative method by distributing questionnaire to developers via online media or physically face-to-face in Seberang Prai Utara (SPU) district in Penang in order to gather the data and achieve the objectives. This research focused on developers in Seberang Prai Utara (SPU) district in Penang as respondent and this study surveys 103 perceptions of developers and a total of 80 (77.7%) respondents had given feedback in the questionnaire. Frequency analysis, descriptive statistic with frequency and crosstabs by SPSS software was used to analyse the data for all objectives. This research found that the main problems and main solutions respectively massive expenditure on capital and proper planning recorded as the highest frequency. Meanwhile, the strongest relationship between the main problems with the main solutions was allocation of total cost for foreign labour with digital technology in IBS. This study may help the developers can successfully adopt IBS technology in achieving affordable housing project, which could help the Malaysian construction industry in achieving affordable housing projects by implementing the solutions given to reduce the costs of IBS technology.